2002
DOI: 10.1159/000067195
|View full text |Cite
|
Sign up to set email alerts
|

The Distribution and Morphological Characteristics of Cholinergic Cells in the Brain of Monotremes as Revealed by ChAT Immunohistochemistry

Abstract: The present study employs choline acetyltransferase (ChAT) immunohistochemistry to identify the cholinergic neuronal population in the central nervous system of the monotremes. Two of the three extant species of monotreme were studied: the platypus (Ornithorhynchus anatinus) and the short-beaked echidna (Tachyglossus aculeatus). The distribution of cholinergic cells in the brain of these two species was virtually identical. Distinct groups of cholinergic cells were observed in the striatum, basal forebrain, ha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

14
106
4

Year Published

2002
2002
2022
2022

Publication Types

Select...
9

Relationship

4
5

Authors

Journals

citations
Cited by 53 publications
(124 citation statements)
references
References 59 publications
14
106
4
Order By: Relevance
“…Choline acetyltransferase immunoreactive neurons (ChAT+) were identified in all these subdivisions, except the cortical interneurons, which were absent in all five species of insectivore studied. The nuclei forming the cholinergic system in these species were similar to that observed in previously studied mammals (Woolf, 1991;Manger et al, 2002a;Dell et al, 2010;Kruger et al, 2010a), but there were a few minor differences. The neurons forming the parabigeminal nucleus (PBg) were either not ChAT immunoreactive or absent in all three shrew species, but were present in the two hedgehog species.…”
Section: Cholinergic Nucleisupporting
confidence: 83%
See 1 more Smart Citation
“…Choline acetyltransferase immunoreactive neurons (ChAT+) were identified in all these subdivisions, except the cortical interneurons, which were absent in all five species of insectivore studied. The nuclei forming the cholinergic system in these species were similar to that observed in previously studied mammals (Woolf, 1991;Manger et al, 2002a;Dell et al, 2010;Kruger et al, 2010a), but there were a few minor differences. The neurons forming the parabigeminal nucleus (PBg) were either not ChAT immunoreactive or absent in all three shrew species, but were present in the two hedgehog species.…”
Section: Cholinergic Nucleisupporting
confidence: 83%
“…The following cranial nerve motor nuclei and other associated nuclei with ChAT immunopositive neurons were found in positions typical of all mammals in all five species (Woolf, 1991;Manger et al, 2002a;Dell et al, 2010;Kruger et al, 2010a): the oculomotor nucleus (III), trochlear nucleus (IV), motor division of trigeminal nerve nucleus (Vmot) (Fig. 4A, 4B), adbucens nucleus (VI), dorsal and ventral subdivisions of the facial nerve nucleus (VIId and VIIv), nucleus ambiguus, dorsal motor vagus nucleus (X), hypoglossal nucleus (XII), the preganglionic motor neurons of the superior salivatory nucleus or facial nerve (pVII), the preganglionic motor neurons of the inferior salivatory nucleus (pIX) and the ventral horn of the spinal cord (vh) (Figs.…”
Section: Cholinergic Cranial Nerve Motor Nucleimentioning
confidence: 96%
“…In the two companion papers to this, regarding cholinergic and serotonergic cells of monotremes [see Manger et al, 2002a, b], we found no such relationship. Woolf [1991] proposed a relationship between cholinergic cell size and brain width, but our comparison [Manger et al, 2002a] does not support this hypothesis. Unfortunately, the data on somatal areas of CA neurons from different species is limited.…”
Section: Somatal Areas Of Catecholaminergic Neuronscontrasting
confidence: 75%
“…These nuclei were found in positions typical of all mammals (Woolf, 1991;Manger et al, 2002a;Maseko et al, 2007;Dell et al, 2010;Kruger et al, 2010). The ChAT+ nucleiidentified in the three Afrotherian species studied include: the oculomotor (III), trochlear (IV), motor division of thetrigeminal (Vmot), adbucens (VI), dorsal and ventral subdivisionsof the facial (VIId and VIIv), nucleus ambiguus, dorsal motor vagus(X), hypoglossal (XII), Edinger-Westphal (EW), medullary tegmentalfield (mtf) andthe preganglionic motor neurons of thesalivatory (pVII) and the glossopharyngeal (pIX) nerves (Figs.…”
Section: Cholinergic Cranial Nerve Motor Nucleimentioning
confidence: 96%